Comparison of post-operative nausea and vomiting with intravenous versus inhalational anesthesia in laparotomic abdominal surgery: a randomized clinical trial - Amiri,Amir Ahmadzadeh (2020)
Abstract Background: Postoperative Nausea and Vomiting (PONV) is a multifactorial surgical complication with an unclear underlying cause. Anesthetic methods, patients' characteristics and the type of surgery are considered as factors affecting PONV. This study was designed to compare the effect of inhalational and intravenous anesthesia in abdominal surgery on the incidence and severity of PONV. Methods: A single-blinded prospective randomized clinical trial on 105 patients aged 18 − 65 years was carried out. Patients were divided into two groups of Total Intravenous Anesthesia (TIVA) and inhalational anesthesia. The incidence and the severity of PONV were examined at 0, 2, 6, 12 and 24 hours after the surgery. The use of a rescue antiemetic was also evaluated. Results: 50.9% of the patients in the inhalation group and 17.3% of the patients in the intravenous group developed PONV (p < 0.001). The incidence of vomiting was reported in 11.3% of the inhalational group and 3.8% of the TIVA group (p = 0.15). 24.5% of patients in the inhalation group and 9.6% of patients in the intravenous group needed an antiemetic medication (p = 0.043). Conclusion: The incidence of postoperative nausea and vomiting and the need for administration of an antiemetic rescue drug and the severity of nausea in patients were significantly lower in the TIVA group.